Environmental graphic design of the great mosque ornaments for Strengthening Demak city branding as the city of wali - Setiawan, Agus; Akrom, Ahmad; Khamadi, Khamadi; Mustaqin, Khairul; Yogananti, Auria Farantika (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This study explores the role of Environmental Graphic Design (EGD) derived from the ornamental heritage of the Great Mosque of Demak in strengthening Demak’s city branding as the “City of Wali” (Kota Wali). Motivated by the need for culturally grounded urban identity amid rapid modernization, the research examines how religious and historical visual elements can be translated into contemporary environmental design. The study adopts a descriptive qualitative approach informed by place branding and visual communication theory. Data were collected through field observations, visual documentation, interviews, and a literature review, followed by an analytical process that involved identifying local wisdom, interpreting mosque ornamentation, evaluating existing EGD practices, and developing and simulating an ornament-based EGD model. The findings indicate that the ornaments of the Great Mosque of Demak possess strong symbolic and communicative value and can be systematically adapted into four key elements of EGD: landmarks, local typography, public advertising media, and wayfinding systems. These components contribute to enhancing urban aesthetics and reinforcing Demak’s religious and cultural identity. Rather than offering a universal solution, the proposed model serves as a context-specific framework that demonstrates how heritage-based visual elements can support culturally and spiritually informed city branding. The study contributes to EGD and place-branding discourse by highlighting the strategic role of local ornamentation in shaping meaningful urban visual identities.